The effect of β-palmitate on intestinal microbiota and immunity during artificial and mixed feeding - Yu. A. Kopanev; A. L. Sokolov (Лечащий Врач)
Background. Breast milk is the best way to feed children in the first year of life, since it performs not only a nutritional function. Hormones, biologically active substances, immune complexes, and living cells of mother's milk have a beneficial effect on the child's body, ensuring the normal course of metabolic processes, maintaining resistance to infections and other adverse external factors. Breast milk helps populate the child's gastrointestinal tract with beneficial microorganisms and prevents the proliferation of pathogenic bacteria. Despite the fact that mother's milk is the preferred way to feed children, this option is not always completely or partially possible, and in this case, children require the introduction of milk formulas as an additional or main diet. Artificial milk formulas, due to understandable production reasons, cannot completely imitate mother's milk. The structure of proteins and the spectrum of oligosaccharides in cow's and goat's milk have slightly different characteristics than similar molecules of breast milk. The original characteristics of vegetable fats, which are used to produce milk formulas, also pose a problem. Some of these technological and biological problems can be solved today, and manufacturers of infant formulas are trying to adapt their composition and functions to breast milk as best as possible.Conclusion. The article discusses such adaptation methods as the use of goat milk and β-palmitate for the production of formulas intended for artificial feeding. In particular, the effect of β-palmitate on the state of the intestinal microflora, and also, indirectly, on immunity, is considered.